Comparison of time and cost between conventional surgical planning and virtual surgical planning in orthognathic surgery in Korea - Si-Yeon Park; Dae-Seok Hwang; Jae-Min Song; Uk-Kyu Kim (SpringerOpen, 2021)
Abstract Background The purpose of this study was to measure the time of the conventional surgical planning (CSP) and virtual surgical planning (VSP) in orthognathic surgery and to compare them in terms of cost. Material and method This is a retrospective study of the patients who underwent orthognathic surgery at the OOOOO University Dental Hospital from December 2017 to August 2018. All the patients were analyzed through both CSP and VSP, and all the surgical stents were fabricated through manual and 3-dimensional (3D) printing. The predictor variables were the planning method (CSP vs. VSP) and the surgery type (group I: Le Fort I osteotomy+bilateral sagittal split osteotomy [LFI+BSSO] or group II: only bilateral sagittal split osteotomy [BSSO]), and the outcomes were the time and cost. The results were analyzed using paired t test. Results Thirty patients (12 females, 18 males) met the inclusion criteria, and 17 patients were excluded from the study due to missing or incomplete data. There were 20 group I patients (LFI+BSSO regardless of genioplasty) and 10 group II patients (BSSO regardless of genioplasty). The average time of CSP for group I was 385±7.8 min, and that for group II was 195±8.33 min. The time reduction rate of VSP compared with CSP was 62.8% in group I and 41.5% in group II. On the other hand, there was no statistically significant cost reduction. Conclusions The time investment in VSP in this study was significantly smaller than that in CSP, and the difference was greater in group I than in group II.